Hydrocephalus - Water on the Brain 2018
DOI: 10.5772/intechopen.73518
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Third Ventriculostomy, Indications and Challenges

Abstract: Endoscopic third ventriculostomy (ETV) allows the cerebrospinal fluid (CSF) to flow directly from the third ventricle through the fashioned ventriculostoma to the interpeduncular cistern, by passing the site of obstruction. In spite of the wide variety of indications where ETV is implemented, its success rate is still debatable especially in certain age groups, where it is most successful in adult patients with obstructive hydrocephalus and it has an identifiable failure rate in children less than 6 months of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…Most authors would agree that coexisting hydrocephalus with CM II should be managed with CSF diversion first, either by shunting or ETV, before consideration is given to posterior fossa decompression [5,6]. With the advent of neuro-endoscopic procedures, more and more cases of hydrocephalus are being treated by ETV to avoid shunt dependence [7,8]. Several authors have reported the success of ETV in the management of hydrocephalus in patients with CM II with good clinical and radiological outcomes [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Most authors would agree that coexisting hydrocephalus with CM II should be managed with CSF diversion first, either by shunting or ETV, before consideration is given to posterior fossa decompression [5,6]. With the advent of neuro-endoscopic procedures, more and more cases of hydrocephalus are being treated by ETV to avoid shunt dependence [7,8]. Several authors have reported the success of ETV in the management of hydrocephalus in patients with CM II with good clinical and radiological outcomes [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Management of hydrocephalus is still a challenging issue because all currently available therapeutic modalities have recognizable failure rates 1,2 . Endoscopic third ventriculostomy (ETV) is a well-established method in the management of hydrocephalus.…”
mentioning
confidence: 99%
“…An ETV Success Score (ETVSS) was initially designed by Kulkarni et al to predict a 6-month outcome with age, etiology, and previous shunt 3 . Accordingly, ETV has the highest success rate for adult patients with obstructive hydrocephalus 1,4–6 . ETV is performed through a frontal burr hole to allow internal inspection and manipulation of the ventricular system.…”
mentioning
confidence: 99%
See 2 more Smart Citations